Study of lichen species growing in the eastern part of Kazakh small mountain hills - Zhumaniyazova, A.; Silybayeva , B.; Bukabayeva , Zh.; Kunanbayeva, N.; Anuarbekova , A. (Fundamental and Experimental Biology, 2025)
The rapid development of industry at the present stage, an increase in the pile of harmful waste substances, the emergence of large settlements, etc. the effects of anthropogenic factors cause climate change around the world. In this regard, it is known that the decrease in atmospheric moisture has a high impact on the increase in the volume of desert zones. The above-mentioned global changes, having a direct impact on living organisms on earth, subject the species composition of any flora and fauna to changes. In this regard, at present, scientists need to pay special attention to the natural changes that have arisen in the local flora. In the research work, the object of study was considered the species of lichen, which make up the main part of the local flora, settled in various biomes, resistant to climatic changes of the external environment with their structure features. In recent years, according to the plant flora of Kazakhstan, in lichenological published scientific studies, you can find data related to the biological characteristics, ecology and use in the indication of species growing in certain areas. There are no specific studies covering the species of lichen found in the flora of the Chingistau, Kalbatau, Kokentau and Abraly mountains, which belong to the "eastern part" of the Kazakh small hills. In the research work, a comparative analysis was carried out, depending on the species composition, since the mountains, given the general name as small mountain hills of the east, considered as an object of study, are located at a long distance from each other. 11 species belonging to 5 genera, combined into 6 family, were identified, growing in all small hills.